Use of Glucocorticoids and Risk of Venous Thromboembolism: A Narrative Review - Simion, Chiara; Campello, Elena; Bensi, Elisa; Bellio, Andrea; Pontarin, Anna; Spiezia, Luca; Simioni, Paolo (Seminars in Thrombosis and Hemostasis, 2021)
Glucocorticoids are potent anti-inflammatory agents that are widely used for the treatment of many inflammatory, autoimmune, and neoplastic disorders. However, their beneficial effect is associated with several side effects, including an increased risk of cardiovascular complications, such as myocardial infarction and stroke. Whether their use also contributes to a procoagulant state, and therefore increases the risk of venous thromboembolism (VTE), is still a matter of debate. As an increased risk of venous thrombotic events is described in patients with Cushing's syndrome, which is characterized by endogenous hypercortisolism, it is reasonable to speculate that the chronic administration of glucocorticoids may induce a hypercoagulable state. However, it seems virtually impossible to separate the role of the drug from the underlying condition, which itself predisposes to the development of VTE. Actually, some evidence suggests that the use of exogenous glucocorticoids for the treatment of underlying disease and its exacerbations may further amplify the risk of VTE. Moreover, a procoagulant state has also been reported in healthy participants receiving oral glucocorticoids versus placebo. We have performed a concise narrative review on available data on the influence of exogenous glucocorticoids on hemostasis and their clinical impact on the risk of VTE.
Keywords: exogenous hypercortisolism; hypercoagulability; inflammation; steroids; thrombosis